1988
DOI: 10.1142/s0217751x88000710
|View full text |Cite
|
Sign up to set email alerts
|

Classical and Quantum Gravity Effects From Planckian Energy Superstring Collisions

Abstract: We argue that superstring collisions at Planckian energies and small deflection angles are calculable through an evaluation and resummation of string loops in flat space-time. This leads to a systematic expansion of the collision in classical general relativity and quantum string effects. Our results explicitly show how unitarity constraints are recovered through loop corrections and how flat metric calculations reveal the generation of nontrivial geometries by energetic particles. Finite-string-size effects c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
522
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 469 publications
(553 citation statements)
references
References 0 publications
29
522
1
Order By: Relevance
“…In [1,2] it was shown that an eikonal resummation of the leading high-energy contributions to the S-matrix leads to results that are fully consistent with general relativity expectations whenever effects due to the finite string size (l s = √ α ) can be neglected. In this particular process the effective geometry turns out to be, to leading order, the wellknown Aichelburg-Sexl (AS) shock-wave metric [11] produced by an energetic pointlike massless particle.…”
Section: Jhep11(2010)100mentioning
confidence: 82%
“…In [1,2] it was shown that an eikonal resummation of the leading high-energy contributions to the S-matrix leads to results that are fully consistent with general relativity expectations whenever effects due to the finite string size (l s = √ α ) can be neglected. In this particular process the effective geometry turns out to be, to leading order, the wellknown Aichelburg-Sexl (AS) shock-wave metric [11] produced by an energetic pointlike massless particle.…”
Section: Jhep11(2010)100mentioning
confidence: 82%
“…First, such strong growth would eventually violate the unitarity bound once E ∼ M D , indicating that a fuller string calculation is required at higher energies, where the emission and exchange of string states is no longer negligible [101][102][103][104][105][106][107][108]. Second, it shows that it is the highest energy KK states that dominate in the cross section, and since these also have the shortest wavelength their properties (and the cross section) is largely insensitive to the details of the higher-dimensional geometry [109].…”
Section: Jhep10(2011)119mentioning
confidence: 99%
“…It can be simplified, however, under the assumption that R p , while comparable or even larger than b, is still smaller than the string length parameter l s , enhanced by a square root of the logarithm of the energy, as we will discuss in more detail in the rest of the paper. 1 When this is the case the eikonal resummation of the leading terms (in energy) of the higher-order string amplitudes [4,11,12] should give a correct representation of the dynamics for every value of the impact parameter, all the way down to b = 0. Although in this limit a geometric interpretation of the brane background is lacking, the dynamics of the string-brane system remains extremely rich and interesting.…”
Section: Jhep03(2016)030mentioning
confidence: 99%
“…The vertex operator for a generic closed string state |ψ can be written as follows: 12) where S andS are labels that identify the little group representations of the left and right part of the closed state, ,¯ the corresponding polarization tensors and 5…”
Section: Jhep03(2016)030mentioning
confidence: 99%
See 1 more Smart Citation